2006
DOI: 10.1152/physiolgenomics.00223.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and nephrotoxic acute renal failure are distinguished by their broad transcriptomic responses

Abstract: Acute renal failure (ARF) has a high morbidity and mortality. In animal ARF models, effective treatments must be administered before or shortly after the insult, limiting their clinical potential. We used microarrays to identify early biomarkers that distinguish ischemic from nephrotoxic ARF or biomarkers that detect both injury types. We compared rat kidney transcriptomes at 2 and 8 h after ischemia/reperfusion and after mercuric chloride. Quality control and statistical analyses were necessary to normalize m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 43 publications
7
64
0
Order By: Relevance
“…(activating transcription factor 3), Lipocalin (LCN2) and TIMP1 (TIMP metallopeptidase inhibitor 1) (Hai et al, 1999, Thukral et al, 2005, Yuen et al, 2006, Sieber et al, 2009) which were described to be affected after kidney injury were found to be strongly up-regulated on mRNA level in our study. The finding of the EGF (epidermal growth factor) down-regulation was in line with the report of Verstrepen et al (1993) and was of interest as EGF downregulation is frequently observed after acute renal failure (Perco et al, 2006).…”
Section: Nephrotoxicitysupporting
confidence: 64%
“…(activating transcription factor 3), Lipocalin (LCN2) and TIMP1 (TIMP metallopeptidase inhibitor 1) (Hai et al, 1999, Thukral et al, 2005, Yuen et al, 2006, Sieber et al, 2009) which were described to be affected after kidney injury were found to be strongly up-regulated on mRNA level in our study. The finding of the EGF (epidermal growth factor) down-regulation was in line with the report of Verstrepen et al (1993) and was of interest as EGF downregulation is frequently observed after acute renal failure (Perco et al, 2006).…”
Section: Nephrotoxicitysupporting
confidence: 64%
“…Up-regulation of ATF3 mRNA was also reported previously to be induced by gentamycin treatment and after ischemic and nephrotoxic acute renal failure (Ozaki et al, 2009, Yuen et al, 2006. We detected 21 known genes common in all 3 concentration treatment group.…”
Section: Discussionsupporting
confidence: 78%
“…To date, broad molecular characterization of AKI models has largely focused on transcriptional profiling of organ-wide signatures (10)(11)(12)(13)(14)(15). Several promising biomarkers have emerged from these studies (16,17).…”
Section: Introductionmentioning
confidence: 99%